2019
DOI: 10.1056/nejmoa1803396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Metagenomic Sequencing for Diagnosis of Meningitis and Encephalitis

Abstract: BACKGROUND Metagenomic next-generation sequencing (NGS) of cerebrospinal fluid (CSF) has the potential to identify a broad range of pathogens in a single test. METHODS In a 1-year, multicenter, prospective study, we investigated the usefulness of metagenomic NGS of CSF for the diagnosis of infectious meningitis and encephalitis in hospitalized patients. All positive tests for pathogens on metagenomic NGS were confirmed by orthogonal laboratory testing. Physician feedback was elicited by teleconferences with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
631
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 703 publications
(710 citation statements)
references
References 28 publications
31
631
8
1
Order By: Relevance
“…A fast and accurate diagnosis would certainly improve prognosis for patients with a suspected CNS infection. Identification of a specific virus provides relevant information on how to treat a patient; therefore, the development of modern technologies, such as high throughput sequencing (Next Generation Sequencing) are warranted as it represents a potentially unbiased marvelous tool for rapid and robust diagnosis of unexplained encephalitis or other types of encephalopathies or neuronal manifestations, especially in the context where more traditional techniques have failed to identify the etiological agent [21,108,111,244,321,322]. Therefore, although our attention is mainly on a few different viruses such as HSV, arboviruses and enteroviruses, it may now be the time to look at CNS viral infection from another perspective.…”
Section: Resultsmentioning
confidence: 99%
“…A fast and accurate diagnosis would certainly improve prognosis for patients with a suspected CNS infection. Identification of a specific virus provides relevant information on how to treat a patient; therefore, the development of modern technologies, such as high throughput sequencing (Next Generation Sequencing) are warranted as it represents a potentially unbiased marvelous tool for rapid and robust diagnosis of unexplained encephalitis or other types of encephalopathies or neuronal manifestations, especially in the context where more traditional techniques have failed to identify the etiological agent [21,108,111,244,321,322]. Therefore, although our attention is mainly on a few different viruses such as HSV, arboviruses and enteroviruses, it may now be the time to look at CNS viral infection from another perspective.…”
Section: Resultsmentioning
confidence: 99%
“…At the meantime, 300μl of UTM were sent for a fast, simultaneous, multiplexed real-time reverse transcription nucleic acid amplification assay for qualitative detection and identification of multiple respiratory viral and bacterial nucleic acids in nasopharyngeal swabs using Qiagen ResPlex II V2.0 kit, which including more than 22 Total RNA was extracted using the QIAamp Viral RNA Mini Kit (QIAGEN, Germany), and sent for the metagenomic sequencing. During metagenomic sequencing, RNA was reversetranscribed into cDNA, with which sequencing library was prepared.…”
Section: Data Collectionmentioning
confidence: 99%
“…Traditional testing methods such as PCR, serological typing, bacterial culture and antibody detection, are regarded as the "gold standard" and widely used in ARI diagnosis 6,7 . However, despite an ongoing effort to include multiple pathogens in a single assay 8,9 , it remains difficult to simultaneously identify all potential ARI pathogens and capture new or uncommon respiratory pathogens 10 .Metagenomic next-generation sequencing (mNGS) is an unbiased way of discovering a broad range of infectious agents [11][12][13] , and has been recently introduced into clinical research to investigate the microbial cause of unusual disease cases 14 , perform broad-scale surveys for pathogens in undiagnosed diseases 15,16 , and understand the role of opportunistic infections 17,18 . For example, a study of severe pneumonia revealed that mNGS is both efficient and reliable 19,20 .…”
mentioning
confidence: 99%